The Nuclear Pore Complex acts as a hub for pri-miRNA transcription and processing in plants - Gonzalo, Lucía (2024)
The regulation of miRNA biogenesis and movement is essential for plant development and environmental responses. HASTY (HST), a karyopherin protein, has been implicated in miRNA biogenesis and movement, though its role in non-cell-autonomous miRNA movement remains unclear. Through a genetic screen, we identified that mutations in the HAWAIIAN SKIRT (HWS) gene suppress the developmental defects of hst mutants by restoring miRNA movement. Our findings show that HWS interacts with nuclear transport factors and nuclear pore complex (NPC) components, including NUP1, positioning HWS as a regulator of miRNA nuclear export. Using microscopy and fluorescence in situ hybridization, we showed that pri-miRNA transcription, and likely their co-transcriptional processing, occurs at the nuclear pore. Notably, we uncovered an antagonistic relationship between HST and HWS in regulating MIRNA transcription at the NPC and AGO1 loading, which could explain the observed changes in miRNA movement. HST promotes the association of MIRNA loci with the NPC, likely facilitating co-transcriptional processing, while HWS negatively regulates this process by targeting MEDIATOR complex subunits to degradation detaching, consequently, the processing complex from the NPC. Furthermore, our data provides evidence of spatial coordination of miRNA transcription, biogenesis, and movement highlighting a novel role for the NPC in the miRNA pathway.